Buckling analysis on various material profiles for truck chassis of ladder frame type - Chau Trung Tin; Hla Myo Tun (Researcher and Lecturer Society, 2022)
Chassis is the most important part of a truck, because it is closely related to the safety and weight of the truck. The profiles used for truck chassis differ as follows: C-channel, U-channel and rectangular tube. This study aims to reveal the most ideal profile for use as a truck chassis. The study was conducted using finite element analysis. The study conducted was buckling analysis. The variables observed for each test profile are free vibration, buckling safety factor, and deformation scale. the C channel profile is most ideal for use as a truck chassis. The simulation results show that the C channel profile has a buckling safety factor > 1 and the smallest average deformation occurs in each shape mode. The U channel profile has a light weight, but the deformation that occurs in each shape is greater than that of the C channel. The rectangular tube profile has the greatest safety factor in each shape mode, but has the largest deformation scale and weight.